U.S. CENTRAL ASIAN POLICY UNDER PRESIDENT BARACK OBAMA - LAUMULIN, Murat (CENTRAL ASIA AND THE CAUCASUS, 2010)
There can be no doubt that during the eighteen months it has been in power, the Obama Administration has in due course defined the main vectors and priorities of U.S. foreign policy, determined the country’s key geopolitical interests, drawn up and adopted a National Security Strategy, and compiled a Nuclear Policy Review.The following factors are having an impact on U.S. policy in the post-Soviet expanse, which includes Central Asia (CA): relations with Russia, the PRC, the Islamic Republic of Iran (IRI), Turkey, Pakistan, and India; the military operation in Afghanistan; NATO’s enlargement; the energy factor; the coordination strategy between the West and the European Union (EU); and the problem of radical Islam.Since the beginning of his presidency, Barack Obama has designated intensification of the U.S.’s influence in the Asia Pacific Region (APR) and further development of relations with China as the priority vectors of his foreign policy.In order to help the American economy recover from its severe crisis, the U.S. tried to create a geopolitical alliance with the PRC (a duumvirate of world administration), but Beijing rejected this proposal. Another main issue (apart from recovery from the crisis) for the Obama Administration is bringing the war on so-called international terrorism (meaning the military operation in Afghanistan in particular) to its successful conclusion. This means that the foreign policy strategy of the present-day American Democrats hinges on the geopolitical situation in Central Asia, while also keeping in mind Russia’s interests. The current U.S. administration is keeping a close strategic eye on the Central Asian region, particularly after the events in Kyrgyzstan. This is posing both new threats and new opportunities for the CA countries in the context of reinforcing the geopolitical balance in the region. A decision was adopted recently to reduce the level of the U.S.’s military presence in Afghanistan with subsequent withdrawal from this country (presumably between 2011 and 2014). If this happens, the security situation in CA, Afghanistan, and Pakistan could drastically change for the worse.It appears that the U.S. is no longer making democratization the fundamental principle of its foreign policy. The Obama Administration realizes that establishing democracy does not boil down to perfunctorily introducing election procedures into a country, but depends on the conditions within the country itself being ripe for such changes and on creating a socioeconomic and political infrastructure, which requires many years of effort. The U.S. intends to make use of “intelligent” power (which presumes a combination of “hard” and “soft” power). Today preference is being given not to combat action, but to political and economic methods, as well as to diplomacy and cultural ties.